Insect Repellants During Pregnancy in the Era of the Zika Virus. Issue 2 (June 2017) - Wylie, B.J.; Hauptman, M.; Woolf, A.D.; Goldman, R.H.
Abstract : ( Obstet Gynecol . 2016;128(5):1111–1115) Research has shown that women affected by the Zika virus during pregnancy suffer from problems such as fetal death, neonatal death, fetal central nervous system lesions, fetal microcephaly, fetal growth restriction, uteroplacental insufficiency, and fetal hearing loss. Hence these patients must be given proper advice so that they can protect themselves against the disease. The objective of this study was to provide relevant information to health providers and patients regarding the use of 2 insect repellants used to prevent the disease, namely N, N-diethylmeta-toluamide (DEET) and permethrin—both of which are US Environmental Protection Agency approved insect repellants.